2012
DOI: 10.1002/hbm.21454
|View full text |Cite
|
Sign up to set email alerts
|

Probing tissue microstructure with restriction spectrum imaging: Histological and theoretical validation

Abstract: Diffusion magnetic resonance imaging (dMRI) is a powerful tool for studying biological tissue microarchitectures in vivo. Recently, there has been increased effort to develop quantitative dMRI methods to probe both length scale and orientation information in diffusion media. Diffusion spectrum imaging (DSI) is one such approach that aims to resolve such information on the basis of the three-dimensional diffusion propagator at each voxel. However, in practice only the orientation component of the propagator fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
331
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(335 citation statements)
references
References 79 publications
4
331
0
Order By: Relevance
“…Computationally expensive nonlinear procedures are normally required to fit such models; however, when the response functions are known (or can be determined) a priori, these models can be efficiently estimated by means of systems of linear equations [27], [29]. Hence, in a voxel, the predicted signal S (q) at q-space location q ∈ R 3 can be expressed as a linear combination with the following general formulation:…”
Section: B Local Forward-modelmentioning
confidence: 99%
“…Computationally expensive nonlinear procedures are normally required to fit such models; however, when the response functions are known (or can be determined) a priori, these models can be efficiently estimated by means of systems of linear equations [27], [29]. Hence, in a voxel, the predicted signal S (q) at q-space location q ∈ R 3 can be expressed as a linear combination with the following general formulation:…”
Section: B Local Forward-modelmentioning
confidence: 99%
“…More complex models with more than three compartments have been proposed, however they come at the cost of prolonged imaging time. Two examples of such models include: (1) composite hindered and restricted model of diffusion (CHARMED) with one anisotropic hindered diffusion compartment and multiple anisotropic restricted compartments for crossing fibers (Assaf and Basser 2005), and (2) restriction spectrum imaging (RSI) with axons modeled by a spectrum of rigid sticks of various sizes (White et al 2013). Neurite Orientation Dispersion and Density imaging (NODDI) models the diffusion-weighted signal as a combination of three basic compartments of CSF, extracellular, and intracellular described above.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that RSI afford finer resolution of molecular diffusion relative to conventional DWI, affording assessment of a gradation of diffusional restrictions, ranging from free to partial restriction to absolute restriction [25]. With RSI, we were able to determine regions of high cellularity within the tumor that failed detection by conventional DWI [26].…”
Section: Restriction Spectrum Imagingmentioning
confidence: 99%